2021
DOI: 10.1002/ana.26082
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrovascular Neuroprotection after Acute Concussion in Adolescents

Abstract: Objective: To assess acute cerebrovascular function in concussed adolescents (14-21 years of age), whether it is related to resting cerebral hemodynamics, and whether it recovers chronically. Methods: Cerebral vasoreactivity and autoregulation, based on middle cerebral artery blood flow velocity, was assessed in 28 concussed participants (≤14 days of injury) and 29 matched controls. The participants in the concussion group returned for an 8-week follow-up assessment. Over the course of those 8-weeks, participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…36 Collectively, these results suggest that high sensitivity of cerebral vasculature to arterial CO 2 may, at least partly, underlie concussion symptoms. Past work from our group indicates the degree of vascular sensitivity to arterial CO 2 (i.e., cerebral vasoactivity) positively relates to the level of concussion symptoms both acutely 14 and chronically 15 after injury. Thus, based on prior data at rest, it stands to reason that high sensitivity to arterial CO 2 results in quick increase in CBF beyond what is needed by neural activity, leading to symptom exacerbation.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…36 Collectively, these results suggest that high sensitivity of cerebral vasculature to arterial CO 2 may, at least partly, underlie concussion symptoms. Past work from our group indicates the degree of vascular sensitivity to arterial CO 2 (i.e., cerebral vasoactivity) positively relates to the level of concussion symptoms both acutely 14 and chronically 15 after injury. Thus, based on prior data at rest, it stands to reason that high sensitivity to arterial CO 2 results in quick increase in CBF beyond what is needed by neural activity, leading to symptom exacerbation.…”
Section: Discussionmentioning
confidence: 91%
“…11 Consequently, during a bout of progressive exercise, arterial CO 2 initially increases, followed by a reduction. 12,13 Our prior work suggested that resting cerebrovascular sensitivity to arterial CO 2 (cerebral vasoactivity) is higher among those who experienced a concussion compared with healthy controls, to a level that is proportional to symptom burden at rest acutely 14 and chronically. 15 Thus, higher cerebrovascular sensitivity to increases in CO 2 during exercise may lead to an increase in CBF beyond what is needed to meet the metabolic demand, and this may underlie exercise-related symptom exacerbation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One possible contributing factor to dizziness after concussion is cerebrovascular dysfunction, specifically impaired cerebrovascular autoregulation, leading to decreased blood flow to the brain (36). Impaired cerebrovascular regulation has been observed within 2 wk of concussion and relates to symptom burden in the subacute concussion phase (37). A gradual reintroduction of exercise may help regulate cerebral blood flow, as researchers observed an association between greater physical activity volume and more improvement in cerebrovascular function during concussion recovery (37).…”
Section: Discussionmentioning
confidence: 99%
“…Impaired cerebrovascular regulation has been observed within 2 wk of concussion and relates to symptom burden in the subacute concussion phase (37). A gradual reintroduction of exercise may help regulate cerebral blood flow, as researchers observed an association between greater physical activity volume and more improvement in cerebrovascular function during concussion recovery (37). The beneficial effect of exercise on cerebrovascular function may also help improve dizziness after concussion (36).…”
Section: Discussionmentioning
confidence: 99%